The Influence of Solvency to the Profitability by Mediation of Activity Ratio in IDX Agricultural Sector - Perdana, Mila Dinda Putri; Gede Ustriyana, I Nyoman; Anak.Agung.Ayu Wulandira Sawitri Djelant, Anak (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021DO - 10.24843/SOCA.2021.v15.i03.p14, 2021)
The strengthening of natural resource governance in Indonesia had result a positive trend in the gross domestic product of the agricultural sector which made it more important and strategic. However, the performance of the agricultural sector in the stock market was in contrast to the contribution of the agricultural sector in Indonesia's Gross Domestic Product. The aim of this research was to find the dominance of solvency on profitability through the mediation of activity ratios. Quantitative data was processed using the causal associative method with moderating variables. The research results showed that there was a moderate and negative connection between solvency and profitability. Solvency was significant on profitability. Solvency experienced a reduction in the regression coefficient after the presence of mediation variable. There was a partial significance on solvency and activity ratio to the profitability. Thus, the activity ratio had a significant effect and was able to become a mediating variable on solvency to the profitability.